A comparative analysis of student usage of the Virtual Learning Environment Moodle in AIT in 2009 and 2011 - Faherty, Sheila; Tunku Ahmad, Tunku Badariah; Harding, Nuala (2013)

(untitled)
This presentation describes the changing patterns of AIT students' usage of the Moodle VLE from 2009 to 2011. Data were gathered from two online surveys in 2009 and 2011 and analyzed just descriptively to see the shift in VLE use.